Peran Perempuan dalam Pembangunan Ekonomi Biru Kepulauan Selayar - Nurul, Nurul Wahida Zal-Zabila; Nur, Andi Cudai (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
This research examines the role of women in developing the blue economy in the Selayar Islands, South Sulawesi. The blue economy, which emphasizes the sustainable use of marine resources, is particularly relevant in this region which is rich in biodiversity and dependent on the fisheries sector. Women make significant contributions as fishermen, fish farmers and seafood processors, despite facing challenges such as gender discrimination and limited access to training. The application of zero waste principles in fish waste management is expected to improve the welfare of coastal communities while maintaining the sustainability of marine ecosystems. Regulatory support from the government, such as the Minister of Maritime Affairs and Fisheries Regulation, is a key factor in empowering women and developing an inclusive local economy. This research shows that empowering women and implementing the blue economy can create a sustainable development model in the Selayar Islands. Keywords: The Role of Women, Blue Economy, Zero Waste